Nutrition in medical education in Latin America: Results of a cross‐sectional survey. Issue 1 (22nd April 2021) - Cardenas, Diana; Díaz, Gustavo; Cadavid, Jessika; Lipovestky, Fernando; Canicoba, Marisa; Sánchez, Paola; Álvarez, Ludwig; Duarte, Yan; Reyes, José Guillermo Gutiérrez; de Noyola, Gilda Miranda; Maza, Claudia; Porbén, Sergio Santana; et al.
Abstract: Rationale: The gap between the nutrition education provided to medical students and the nutrition competences and attitudes needed for doctors to provide effective nutrition care is a global concern. The goal of this study was to investigate the curricular content on nutrition education in Latin American medical schools and to evaluate the self‐perceived knowledge, attitudes, and barriers to nutrition practice of final‐year medical students. Methods: Eighty‐five public and private medical schools from 17 Latin American countries were invited to participate in the study. Two close‐ended online questionnaires consisting of 25 and 43 questions were sent to medical school directors. Quantitative variables were expressed as frequencies, percentages, mean ± standard deviation, medians, and ranges. Results: A total of 22 (26%) medical school directors responded, of which 11 schools (50%) offered stand‐alone mandatory nutrition courses in preclinical and 8 (36%) in clinical years. The mean hours dedicated to nutrition education was 47 (range: 0–150). A total of 1530 of 1630 (94%) students from 12 countries responded. Students' average age was 25 ± 3 years, and 59% were female. Most students agreed that improving patients' health through nutrition (91%) is important and that nutrition counseling and assessment should be part of routine care provided by all physicians (89%), but they lack the level of education and training required to address nutrition‐related issues. Conclusions: Positive attitude and interest in nutrition among final‐year medical students is high, but nutrition education is not perceived as sufficient to adequately prepare doctors in the field of nutrition.